The design of simulated moving bed chiral separation using the concept of separation volume - Rodrigues, Alírio (2010)
This paper deals with chiral separation by simulated moving bed chromatography when mass transfer resistances are negligible, equilibrium theory provides explicit criteria for the choice of the SMB operating conditions should be evaluated through simulation. Using a package based on the analogy with the true moving bed operation, this work shows how mass transfer resistance can effect the conditions for enantiomers separation, as well as the critical valves stated by equilibrium theory. The concept of separation volumes is applied to show how the flow-rate constraints, in presence of mass transfer resistances, have to be modified.